2014
DOI: 10.1371/journal.pone.0100856
|View full text |Cite
|
Sign up to set email alerts
|

Natural Mineral Particles Are Cytotoxic to Rainbow Trout Gill Epithelial Cells In Vitro

Abstract: Worldwide increases in fluvial fine sediment are a threat to aquatic animal health. Fluvial fine sediment is always a mixture of particles whose mineralogical composition differs depending on the sediment source and catchment area geology. Nonetheless, whether particle impact in aquatic organisms differs between mineral species remains to be investigated. This study applied an in vitro approach to evaluate cytotoxicity and uptake of four common fluvial mineral particles (quartz, feldspar, mica, and kaolin; con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 81 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…Min-U-Sil, or α-quartz, is very toxic as a crystalline material which is thoroughly noted in the toxicological literature, and why it was implemented in these studies as a positive control. 37 The EPR data demonstrate that a large amount of radicals can arise from a very small surface area of the material (~7 m 2 /g) for quartz. This implies that perhaps it is its capability to produce large amounts of free radicals that results in such potent toxic effects in biological systems.…”
Section: Resultsmentioning
confidence: 95%
“…Min-U-Sil, or α-quartz, is very toxic as a crystalline material which is thoroughly noted in the toxicological literature, and why it was implemented in these studies as a positive control. 37 The EPR data demonstrate that a large amount of radicals can arise from a very small surface area of the material (~7 m 2 /g) for quartz. This implies that perhaps it is its capability to produce large amounts of free radicals that results in such potent toxic effects in biological systems.…”
Section: Resultsmentioning
confidence: 95%
“…High concentrations of SPM can accumulate in the gills, disturb the respiratory function, and have been found to translocate into epithelial cells, cause lipid peroxidation, and reduce the tolerance of infection by pathogens [67,68]. Additionally, studies with gill epithelial cells (rainbow trout, RTgill-W1) and fluvial fine sediment revealed translocation of fine minerals (<2 μm, 10-250 mg L À1 ) into the cells as well as material-related cytotoxicity [69]. Here, quartz and feldspar only caused sporadic changes in biomarker response, and exposure to mica (silicate minerals) and kaolin induced cytotoxicity as well as free radicals and cell membrane damage.…”
Section: Fishmentioning
confidence: 99%
“…Here, quartz and feldspar only caused sporadic changes in biomarker response, and exposure to mica (silicate minerals) and kaolin induced cytotoxicity as well as free radicals and cell membrane damage. Therefore, Michel et al [69] conclude that the uptake of fine particles by gill epithelial cells is a common natural event in aquatic species with the material, size, shape, and concentration determining the impacts.…”
Section: Fishmentioning
confidence: 99%
“…Other studies have shown the elevated HA of clays: kaolinite and bentonite (a montmorillonite-rich deposit, commonly formed from the weathering of volcanic ash) were found to be as haemolytic as crystalline silica (Min-U-Sil), whereas feldspar (a mineral commonly found in soil samples) was less haemolytic (e.g., [50]). Phyllosilicate minerals were also found to be cytotoxic in other in vitro assays, for example a recent study on rainbow trout gill epithelial cells established that the phyllosilicates, mica and kaolinite, were markedly more cytotoxic than the two framework silicates (quartz and feldspar) tested ([51]).…”
Section: Discussionmentioning
confidence: 99%